PELATIHAN PENGGUNAAN MEDIA PEMBELAJARAN DENGAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) PADA GURU EKONOMI SMA TAMAN SISWA PADANG - Stevani Stevani; Vivina Eprillison Eprillison; Dona Darmayuni; Yuli Diniyah Zulbakri (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2022)
One of the efforts made to educate the life of the nation is in an innovative way that must be applied in the learning process, one of which is by doing the teaching and learning process. Teachers are required to be able to carry out the learning process, learning evaluation, mastery of technology and information, the application of various learning models, one of which is with the CTL learning model and the use of learning media, including using canva applications, wordpress and other applications. The application of canva and wordpress applications can help teachers in delivering learning materials in a more interactive manner, thus enabling teaching and learning activities to be more productive and meaningful by simplifying tasks, increasing collaboration, and fostering communication. Learning media applications using canva and wordpress applications are felt very needed by teachers in the learning process because this type of media adapts to the present era in the era of society 5.0. The goal to be achieved in doing this activity is to provide training for teachers related to the use of learning media and also provide valuable experiences for teachers, especially the application of CTL learning models in the creation of learning media with the use of canva and wordpress applications in Taman Siswa Padang High School.